Pengaruh Efektivitas Pelatihan Dan Kompetensi Karyawan Terhadap Kinerja Karyawan Pada PT Bank BNI KC Melawai Raya Jakarta Selatan - Geafiska Dianofan; Mitri Nelsi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to determine the effect of training effectiveness and employee competency on employee performance at PT Bank BNI KC Melawai Raya South Jakarta partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling, namely 96 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that training effectiveness has a significant effect on employee performance with the regression equation Y = 14,689 + 0,619X1, a correlation coefficient value of 0,678 (strong), a determination coefficient of 46.0% and a hypothesis test obtained t count > t table, namely (8,943 > 1.986). Employee competence significantly influences employee performance, as shown in the regression equation Y = 17,744 + 0,546X2, a correlation coefficient of 0,602 (strong), and a coefficient of determination of 36.3%. The hypothesis test yielded a calculated t-value > t-table value (7,316 > 1.986). Training effectiveness and employee competence simultaneously significantly influence employee performance, as shown in the regression equation Y = 8,363 + 0,463X1 + 0,329X2. The correlation coefficient was 0,750 (strong), and the coefficient of determination was 56.2%, while the remaining 43.8% was influenced by other variables. The hypothesis test yielded a calculated F-value > F-table value (59,730 > 3.090)..